Pokémon. Sword & shield. Volume 9 - Kusaka, Hidenori; Tanzer, Molly (Pokémon sword & shield ;, 2024)
Casey Shield, a hacker who invented the Dynamax Simulator, and Henry Sword, a boy who repairs gear for Pokémon, both dream of entering the Galar region's Gym battles. For Casey, it's a chance to reunite with her lost Pokémon. For Henry, it's an opportunity to search for the legendary Rusted Sword and Rusted Shield. Eternatus, the Gigantic Pokémon, has appeared! And with Galar in chaos due to the Gigantamax phenomenon occuring all over the region, Henry and Casey's only hope of defeating Eternatus--and stopping the Gigantamax evolutions--is with the help of two powerful Pokémon--Zacian and Zamazenta!!"--Back cover.